Severe influenza A virus pneumonia complicated with Curvularia lunata infection: Case Report - Zhang, Yanqing; Li, Haixia; Chen, Ling; Feng, Fei; Liu, Liping; Guo, Qinghong (Frontiers in Cellular and Infection Microbiology, 2023)
Human infection with Curvularia lunata (C. lunata) is exceptionally rare. A 23-year-old female patient contracted both bacterial and Curvularia lunata infections during influenza A virus infection. Multiple etiological tests were performed repeatedly during hospitalization due to fluctuations in condition. On the 17th day after hospital admission, mold hyphae were discovered in the pathogen culture of the patient’s bronchoalveolar lavage fluid during one of these examinations. The patient was suspected to have a filamentous fungal infection. Consequently, we further obtained sputum samples for fungal culture, which confirmed the diagnosis of Curvularia infection. The patient, in this case, was in a critical condition, experiencing complications of lung abscess, pneumothorax, sepsis, and multiorgan failure. Despite prompt initiation of antifungal therapy including amphotericin B cholesteryl sulfate complex and isavuconazole upon detection of the fungal infection and concurrent administration of active organ function support treatment, the patient’s condition rapidly deteriorated due to compromised immune function. Ultimately, on the 27th day of treatment, the patient succumbed to septic shock and multiple organ dysfunction syndrome. This is the first case of Curvularia lunata infection in our hospital. In this paper, we aim to raise awareness of Curvularia lunata infection and to emphasize that the possibility of this fungal infection should be considered in patients with severe pneumonia caused by influenza A virus and that empirical antifungal therapy should be given promptly when the patient has invasive lung damage.